Hybrid deliberative democracy in practice: a case study of community engagement and public decision-making in Malang City, Indonesia - Nurjaman, Asep; Pinto, Julio Tomas (Frontiers in Political Science, 2025)
This study investigates the implementation of deliberative democracy at the local level in Indonesia, focusing on how community participation shapes democratic development in a developing-country context. Although the concept of deliberative democracy has been widely discussed in Western scholarship, empirical research in Global South settings remains limited. A qualitative research approach—comprising in-depth interviews, field observations, and document analysis—was employed to explore how public forums, participatory planning, and citizen panels contribute to local policymaking in Malang City. Findings show that these participatory mechanisms enhance inclusiveness, responsiveness, and citizen empowerment. However, their effectiveness is constrained by persistent structural limitations, including elite dominance, low political literacy, and fragmented institutional support. These dynamics have produced a hybrid form of deliberation that bridges informal community networks, formal participatory institutions, and local political practices. The study demonstrates that deliberative democracy in the Global South is best understood as a context-dependent process shaped by cultural norms and institutional arrangements rather than a purely normative ideal. The results highlight the need for comparative analyses that incorporate socio-political diversity across developing democracies. Overall, this research contributes to global debates on deliberative democracy and offers practical insights for enhancing participatory governance in transitional political environments.